The Analysis of Water Sub Critical Hydrolysis Conditions on Content in Fatty Methyl Ester Biodiesel Production by Supercritical Methanol Method - Argo, Bambang Dwi; Swastomo, Budi (Jurnal Teknologi Pertanian, 2010)
Biodiesel is an alternative fuel with a fatty acid ester composition made from raw vegetable oils/animal that has characteristics similar to diesel oil. High quality biodiesel fuel from oil/fat had been processed by two-stage supercritical metanol method which consisted of the hydrolysis process by mixing oil and water in sub-critical conditions that generated free fatty acids and glycerol, followed by esterification process that mixed free fatty acids with methanol in supercritical methanol conditions. In this research, hydrolysis of frying oil at sub-critical conditions had been conducted in various conditions. The conditions were the ration of oil to water and hydrolysis time in the reactor chamber at sub-critical condition. Materials used in this research were commercial frying cooking oil and bottled water. The purpose of this study was to find out the effect of hydrolysis at sub-critical condition on free fatty acids content generated in the production of biodiesel using super critical methanol. The results showed that there was an increasing percentage of ALB in the hydrolysis reaction with sub-critical water conditions. The highest and significant ALB was 67.10% that obtained in ratio of water to oil 25:75 and holding time of 20 minutes. Fatty acid produced in super-critical reactor was solid at room temperature and the behavior of this product still required a thermal analysis for designing exhausting pipe from the reactor in order to prevent blockage.Keywords: Biodiesel, hydrolysis, sub-critical, free fatty acids